Prevention and Treatment of Hardware-Related Infections in Deep Brain Stimulation Surgeries: A Retrospective and Historical Controlled Study - Li, Jiping; Zhang, Wenjie; Mei, Shanshan; Qiao, Liang; Wang, Yunpeng; Zhang, Xiaohua; Li, Jianyu; Hu, Yongsheng; Jia, Xiaofei; Zhang, Yuqing (Frontiers in Human Neuroscience, 2021)
Background Hardware-related infection in deep brain stimulation (DBS) is a most commonly reported complication frequently resulting in removal of implantable pulse generator (IPG). Objective The aim of this study is to establish a useful strategy to better prevent and treat those infections and to improve the preservation rates of IPG. Methods We conducted a retrospective and historical controlled study of all adult patients (≥18 years old) who had undergone initial DBS implantation at a single center. All participants were enrolled into control group (between June 2005 and June 2014) or intervention group (between July 2014 and May 2019) based on their surgery dates. We used the intraoperative irrigation with hydrogen dioxide solution in the intervention group. On basis of dates of diagnosis, patients with hardware-related infection after DBS were enrolled into group A (between June 2005 and June 2014) or group B (between July 2014 and May 2019). IPG-sparing algorithm (Isa) was applied for group B. The early onset IPG infections of control and intervention group were evaluated. The IPG preservation rates in both groups A and B were statistical analyzed. Results Six cases of early IPG infection and subsequent IPG removal occurred in control group, while none occurred after intraoperative usage of the hydrogen dioxide in intervention group; IPG preservation rate of infected cases in group B was significantly higher than that in group A (70% vs.16%, P= 0.004). Conclusion The combined application of hydrogen dioxide solution and Isa seems to be an effective strategy to prevent IPG infection.